The influence of Hall currents on unsteady-MHD heat transfer flowin a conducting channelcontaining two ionized fluids - Rao, Gowri Sankara V.; Raju, Linga T. (Zielona Góra: Uniwersytet Zielonogórski)
We delve into the effects of hall currents on the dynamics of unsteady magnetohydrodynamic flow and heat transfer within a two-fluid system of ionized gases confined within a horizontal channel bounded by parallel conducting plates. Employing a regular perturbation technique, we solve the governing partial differential equations to unveil the distributions of velocity and temperature, alongside profiles depicting heat transfer coefficients.
Keywords: Hall effect; magnetohydrodynamic (MHD); plasma dynamics; heat transfer; immiscible flow; conductive porous plates; regular perturbation method